2019
DOI: 10.1021/acsomega.9b01702
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Mycotoxins in Extruded Commercial Cat Food

Abstract: The occurrence of the most important mycotoxins (deoxynivalenol, fumonisin B 1 and B 2 , aflatoxins B 1 , B 2 , G 1 , and G 2 , ochratoxin A, zearalenone, T-2, and HT-2 toxins) was determined in 64 extruded cat foods purchased in Italy through ultra-performance liquid chromatography coupled with tandem mass spectrometry. Deoxynivalenol and fumonisins were the most common con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…None exceeded the 50ppb and 20 ppb/kg limits established by Brazilian legislation and the Pet Food Brazil Manual of the Brazilian Association of the Pet Products Industry (ABINPET, 2017). Grandi et al (2019) observed that a relatively high number of samples (five samples of premium feeds and three samples of standard feeds for adult cats) exceeded the limits established for some mycotoxins. The occurrence of aflatoxins in pet food is highly variable.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…None exceeded the 50ppb and 20 ppb/kg limits established by Brazilian legislation and the Pet Food Brazil Manual of the Brazilian Association of the Pet Products Industry (ABINPET, 2017). Grandi et al (2019) observed that a relatively high number of samples (five samples of premium feeds and three samples of standard feeds for adult cats) exceeded the limits established for some mycotoxins. The occurrence of aflatoxins in pet food is highly variable.…”
Section: Resultsmentioning
confidence: 93%
“…The ingredients most often found in commercial cat food were offal meal, present in 100% commercial food; followed by corn and broken rice, present in 90% food; corn gluten meal 60, beer yeast, chicken fat; occurring in 80%, 70% and 60% of complete cat foods evaluated in this study, respectively. The choice of raw materials used in the formulation and the impact of processing on cat food is extremely important, and the quality of the final product is attributed to the texture, uniformity, extrusion process, nutritional quality and economic viability of the product (Grandi et al ., 2019). Thus, the processing of the ingredients is essential to increase the digestibility of the ingredients in the feed.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the specific hormonal regulation of reproductive processes in bitches, which involves long progesterone and prolactin cycles and high sensitivity to endogenous and exogenous estrogens, is believed to have an important role in the etiopathogenesis of those disorders [177,178]. Experimental studies showed that ZEA, a mycoestrogen often found in pet food [179][180][181], affects female reproductive organs [19,182]. Changes in bitches' reproductive systems were mainly in the ovaries and the uterus, including the degeneration of cells, inhibition of biological activity in the ovaries, and edema and extravasations in the uterus [18].…”
Section: Reproductive Disordersmentioning
confidence: 99%
“…More recently, following some scientific opinions provided by the European Food Safety Authority (EFSA), specific "guidance values" recommended for DON, ZEA, OTA, T-2, and HT-2 also referred to the compound feed intended for dogs or cats have been introduced (Grandi et al 2019).…”
Section: Legislation On Mycotoxins In Dry Pet Foodmentioning
confidence: 99%